Paris in the poetic imaginary of Italo Calvino - Carmelitano, Luigi (Ángulo Recto. Revista de estudios sobre la ciudad como espacio plural, 2013)
This article analyzes the impact of the city of Paris in poetic imagery of Italo Calvino, reviewing some of his most representative fictions and essays, without leaving aside the role that this capital has played in his biography. It emerges a multifaceted city full of literary and cultural references, which have a deep influence on Calvino’s poetic imaginary, thus resulting very productive for his writing prose.